THE EFFECT OF USING JIGSAW METHOD ON THE ABILITY OF THE FIRST YEAR STUDENTS OF SMA PGRI PEKANBARU IN COMPREHENDING NARRATIVE TEXTS - Alfani, Heppy Nanda; Ras, Fakhri; Erni, Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aimed to find out the effect of using Jigsaw method on the ability of the first year students of SMA PGRI Pekanbaru in comprehending narrative texts. This is a pre-experimental research conducted by using a pre-test – treatment – post-test design.. The population of this study was the first year students of SMA PGRI Pekanbaru which consisted of 3 classes with the total of 115 students. The sample of this study was X.2 of social science class with 40 students.The writer, during treat the students, found that students’ motivation to read the text increase. Besides, students got more confidences to split out their opinion while discussion and present the result in front of the class. After treatment was held, the writer distributed the tests. The instrument of the research was a reading test with multiple choice type. The result showed a strong correlation between Jigsaw method and students’ reading comprehension. The results of data analysis showed that the mean score of pre-test was 64.03, and the mean score of post-test was 82.00. Based on the data analysis, it can be concluded that there is a significant difference between the pre-test and the post-test because the t-test observed was higher than t-table. In other words, the alternative hypothesis of this research was accepted. It means that Jigsaw method can be used as an alternative strategy in the teaching of reading.Keywords: Jigsaw, Reading Comprehension, Narrative Text